PENTINGNYA MEMAHAMI PENERAPAN PRIVASI DI ERA TEKNOLOGI INFORMASI - Imam Teguh Islamy; Sisca Threecya Agatha; Rezky Ameron; Berry Humaidi Fuad; Evan Evan; Nur Aini Rakhmawati (Universitas Negeri Padang, 2018)
Privacy is the ability of one or a group of individuals to close or protect their lives and personal affairs from the public, or to control the flow of information about themselves. Privacy is inherent in every human being and deserves respect. In the current era of information technology, the privacy of one's data has been widely spread through the internet. Without realizing it, a lot of data about someone's privacy has been leaked on the internet. Spread privacy data can be caused by our negligence or service providers. It is not wrong if there is a view that says that in this information technology era, privacy issues are not a big problem. But we need to know that actually privacy data on the internet can pose a threat to crime both for ourselves and our families. The purpose of making this paper is to remind the public that the development of information technology, then our privacy data will also be more open. Therefore, the author expects the public to be able to sort out what data and to whom the data will be given so there is no abuse. In addition, the community also needs to understand and support the laws and regulations concerning privacy that have been regulated by the government so as not to exceed the privacy limits of themselves and others